Semiotics from a Media Ecology Point of View and McLuhan’s Notion that “The Medium is the Message”: A Probe - Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2023)
Semiotics and media ecology are compared and an attempt is made to reconcile semiotics and media ecology and translate the terminology of semiotics into that of media ecology and vice versa that of media ecology into semiotics. An attempt is also made to create a bridge between these two closely related studies of communication to create a hybrid study of the media ecology of semiotics and the semiotics of media ecology.